Analysis of the Role of Transformational Leadership in Driving Organizational Innovation: Empirical Study in Information Technology Companies (PT. Mahaka Media Tbk Transforms into MahakaX) - Wibowo, Teguh Setiawan; Iriantini, Dwi Bhakti (PT FORMOSA CENDEKIA GLOBAL, 2024)
With the current increasingly high development of information technology, the level of competition faced by organizations, especially for business activities with the aim of seeking maximum profits (profit oriented companies), is felt to be increasingly high and the competition is also getting tighter. The research objective is to analyze the role of transformational leadership in encouraging organizational innovation. The method used is descriptive analysis supported by data from internet searching or online-based literature in the form of journals, websites and others. The result is that there are 10 (ten) roles of transformational leadership in encouraging organizational innovation which are based on transformational leadership as the